Homozygous c.130–131 ins A (pW44X) mutation in the HAX1 gene as the most common cause of congenital neutropenia in Turkey: Report from the Turkish Severe Congenital Neutropenia Registry. Issue 10 (19th July 2019) - Yılmaz Karapınar, Deniz; Patıroğlu, Türkan; Metin, Ayşe; Çalışkan, Ümran; Celkan, Tiraje; Yılmaz, Barış; Karakaş, Zeynep; Karapınar, Tuba H.; Akıncı, Burcu; Özkınay, Ferda; Onay, Hüseyin; Yeşilipek, Mehmet Akif; et al.
Abstract: Background: Severe congenital neutropenia is a rare disease, and autosomal dominantly inherited ELANE mutation is the most frequently observed genetic defect in the registries from North America and Western Europe. However, in eastern countries where consanguineous marriages are common, autosomal recessive forms might be more frequent. Method: Two hundred and sixteen patients with severe congenital neutropenia from 28 different pediatric centers in Turkey were registered. Results: The most frequently observed mutation was HAX1 mutation ( n = 78, 36.1%). A heterozygous ELANE mutation was detected in 29 patients (13.4%) in our cohort. Biallelic mutations of G6PC3 ( n = 9, 4.3%), CSF3R ( n = 6, 2.9%), and JAGN1 ( n = 2, 1%) were also observed. Granulocyte colony‐stimulating factor treatment was given to 174 patients (80.6%). Two patients died with infectious complications, and five patients developed myelodysplastic syndrome/acute myeloblastic leukemia. The mean (± mean standard error) follow‐up period was 129.7 ± 76.3 months, and overall survival was 96.8% (CI, 94.4–99.1%) at the age of 15 years. In Turkey, severe congenital neutropenia mostly resulted from the p W44X mutation in the HAX1 gene. Conclusion: In Turkey, mutation analysis should be started with HAX1, and if this is negative, ELANE and G6PC3 should be checked. Because of the very high percentage of consanguineous marriage, rare mutations should be tested in patients with a negative mutation screen.